Time-resolved plastic scintillator dosimetry in MR linear accelerators without image distortion. (June 2022) - Klavsen, M.F.; Ankjærgaard, C.; Behrens, C.P.; Vogelius, I.R.; Boye, K.; Hansen, R. Hvass; Andersen, C.E.
Abstract: One of the newest developments within radiotherapy is the integration of Magnetic Resonance (MR) scanners and Megavoltage X-rays from linear accelerators into the new MR-Linacs. Some MR-Linacs are able to perform gated treatments based on continuously acquired 2D MR images taken during dose delivery, which has the potential to reduce margins required for tumor coverage. We have developed a dosimetry system that can provide time-resolved, dose-per-pulse, dosimetry without distorting the MR images in order to characterize this technology. The system is based on a plastic BCF-60 scintillation detector (PSD) coupled to an optical PMMA fiber cable. The detector was placed in a plastic tube filled with water and inserted into the piston of a dynamic MRI compatible phantom to be treated on a ViewRay MRIdian 0.35 T MR-Linac. The piston performed a sinusoidal movement to simulate a breathing cycle of either 4 or 8 s. We demonstrate that the detector system is able to provide real-time dose-per-pulse measurements without causing distortions in the MR images. The time-resolved dosimetry system revealed systematic dose rate transients during gated treatments that lasted about 1 s in every gating sequence where the beam turned on and off. Detection of such effects require real time dosimetry which does not interfere with the MRI based gating. Highlights: Plastic scintillator and alanine dosimeters do not show image distortions in MR-Linac. Time-resolved scintillator measurements during gated MR-Linac treatment. Dose transients at the start of every beam on, likely affecting homogeneity of dose delivery. Scintillator and alanine dose measurements agree within (0.17 ± 0.11) Gy.